2006
DOI: 10.1016/j.phytochem.2006.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional content of fresh, bee-collected and stored pollen of Aloe greatheadii var. davyana (Asphodelaceae)

Abstract: Aloe greatheadii var. davyana is the most important indigenous South African bee plant. Fresh, bee-collected and stored pollen of this aloe was collected and analysed for its nutritional content, including amino acid and fatty acid composition. Highly significant differences were found between the three types of pollen. Collection and storage by the bees resulted in increased water (13-21% wet weight) and carbohydrate content (35-61% dry weight), with a resultant decrease in crude protein (51-28% dry weight) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
130
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(154 citation statements)
references
References 31 publications
17
130
2
5
Order By: Relevance
“…The value reported in this study for carbohydrates in pollen samples was similar to that reported by HUMAN & NICOLSON (2006) in fresh pollen from South Africa (34.7%), and SOUZA et al (2004) calculated a mean percentage of 37.5% for glycides in meliponine-collected pollen. The Technical Regulation for bee pollen determines that the total sugar content can vary in the range 14.5-55.0% on a dry weight basis.…”
Section: Carbohydratessupporting
confidence: 90%
“…The value reported in this study for carbohydrates in pollen samples was similar to that reported by HUMAN & NICOLSON (2006) in fresh pollen from South Africa (34.7%), and SOUZA et al (2004) calculated a mean percentage of 37.5% for glycides in meliponine-collected pollen. The Technical Regulation for bee pollen determines that the total sugar content can vary in the range 14.5-55.0% on a dry weight basis.…”
Section: Carbohydratessupporting
confidence: 90%
“…This result is surprising as bees often eat nitrogen rich foods; worker bees routinely ingest amino acid rich pollen (Human and Nicolson, 2006) and may even cannibalise brood under conditions of protein deficit (Schmickl and Crailsheim, 2001). Amino acids are vital for honeybee growth, maintenance and development, for example, foraging bees need to preserve and maintain flight muscles that experience wear and tear during flight (Roberts and Elekonich, 2005) and EAAs are vital building blocks for this protein turnover and repair.…”
Section: Discussionmentioning
confidence: 99%
“…Honeybee-collected pollen provides a rich source of easily digestible protein (Crailsheim et al, 1992;Campos et al, 1996;Serra Bonvehi and Escola Jorda, 1997;Szczęsna, 2006a;b). In addition to proteins, pollen also contains carbohydrates, fats and minerals (Orzáez Villanueva et al, 2002;Szczęsna et al, 2002;Almeida-Muradian et al, 2005;Human and Nicolson, 2006;Szczęsna, 2006a;2007;Campos et al, 2008;Carpes et al, 2009;Martins et al, 2011;Morgano et al, 2012). The chemical composition of bee-pollen showed an average of 7.40% moisture, 20.00% protein, 6.00% lipids, and 2.20% ash (Almeida-Muradian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Different values (4.20, 20.50, 4.90, and 2.90%, respectively) of Brazilian bee-pollen were found by Carpes et al (2009). The chemical composition of bee-pollen is known to vary according to the plant species from which the pollen was collected (Szczęsna et al, 2002;2006a;Morgano et al, 2012), the geographic origin (Serra Bonvehi and Escola Jorda, 1997;Carpes et al, 2009;Martins et al, 2011;Morgano et al, 2012), the season (Szczęsna et al, 2002;Morgano et al, 2012), and the storage and storage method (Human and Nicolson, 2006;Siuda et al, 2012). Bee-pollen was involved in formulating supplementary food products because of its nutritional and therapeutic properties (Iannuzzi, 1993;Campos et al, 1996;Serra Bonvehi and Escola Jorda, 1997;Pernal and Currie, 2000;Orzáez Villanueva et al, 2002;Kacániová et al, 2012;Morgano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%